Efficient conversion of distillers grains as feed ingredient by synergy of probiotics and enzymes - Chen, Kai; Deng, Xiangrong; Jiang, Dahai; Qin, Lanxian; Lu, Mengqi; Jiang, Wenxuan; Yang, Manqi; Zhang, Liangliang; Jiang, Jianchun; Lu, Liming (Frontiers in Microbiology, 2024)
The direct feeding value of distillers grains is low due to the presence of higher cellulose, lignin and anti-nutritional factors such as mannan and xylan. In this study, complex enzymes and probiotic flora based on "probiotic enzyme synergy" technology were used to produce fermented distillers grains. The optimal substrate ratio, moisture content, fermentation time and temperature were determined.Subsequently, scale-up experiments were conducted to determine the performance of fermented feed. The results showed that multi-probiotic (Lactobacillus casei, Bacillus subtilis, Saccharomyces cerevisiae and Aspergillus oryzae) cooperated with complex enzymes (glucanase, mannanase, xylanase) showed excellent fermentation effect, crude protein, trichloroacetic acid soluble protein and fat increased by 31.25%, 36.68% and 49.11% respectively, while crude fiber, acidic fiber and neutral fiber decreased by 34.24%, 26.91% and 33.20% respectively. The anti-nutritional factors mannan and arabinoxylan were reduced by 26.96% and 40.87% respectively. Lactic acid, acetic acid, and propionic acid in the fermented organic acids increased by 240.93%, 76.77%, and 89.47% respectively. Butyric acid increased significantly from scratch, and the mycotoxin degradation effect was not significant. This study provides a potential approach for high-value utilization of distillers grains.